The Oxford French dictionary : - Janes, Michael. (Oxford University Press, 1994)
Complete with over 45,000 words and phrases, this is a revised and updated edition of a popular English-French dictionary. Designed to meet the needs of both English and French speakers, it covers the core vocabulary in each language. With 5% new material, it offers up-to-date translations - including technical vocabulary, many colloquialisms, phrases and example sentences showing words in use. Each entry is clearly labelled to help the user choose the appropriate word or idiomatic expression, and offers pronunciation guidance in the International Phonetic Alphabet. In addition, there are tables of regular and irregular French verbs, and the past tenses and participles of irregular English verbs